Aesthetic Education in the Uzbek Family as the Basis for the Formation of a Harmonious Personality (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article examines the role of the family as the most important social institution in raising children based on Uzbek national traditions. It emphasizes the importance of a harmonious combination of aesthetic, spiritual and cultural values ​​in the development of a child's personality. Key aspects of education are analyzed, including instilling aesthetic taste, respect for art and nature, as well as the use of cultural heritage to form moral ideals. Particular attention is paid to the role of grandparents, as well as the importance of public policy in strengthening family values. A conclusion is made about the importance of aesthetic education as the basis for the formation of future citizens capable of combining national traditions with the challenges of modern society.